Accuracy of a new hysteroscopic method in the assessment of tubal patency: Hysteroscopic Chromotubation - Burak Yucel; Emine Demirel; Sefa Kelekci; Kerem Doga Seckin; Osama Shawki (Medical Network, 2018)
Objective The aim of this study was to evaluate the diagnostic accuracy of hysteroscopic chromopertubation (HCT) in the assessment of tubal patency by comparing its results with laparoscopic chromopertubation (LCT). Study Design The population of this prospective cohort study consisted of both fertile and infertile women. Sixty-four women were included to the study. HCT was assessed by the observation of the transport of highly concentrated methylene blue from uterine cavity to tubal ostia. The results of HCT were compared with the results of LCT as a gold standard. The accuracy of HCT, sensitivity, specificity, positive and negative predictive values in diagnosing tubal patency were calculated. Results The results of HCT and LCT were evaluated for right and left tubes, separately. One hundred and twenty-eight tubes were determined. Sensitivity, specificity, positive and negative predictive values for HCT were; 85.85%, 59.09%, 91% and 46.43%, respectively. Conclusion This study's result showed that HCT had high sensitivity and moderate specificity values in the assessment of tubal patency. HCT during office hysteroscopy could give the chance to practitioners to assess tubal patency without subjecting the patient to multiple procedures.